PENGARUH MEDIA VIRTUAL REALITY TARI DOLANAN PADA MINAT BELAJAR EKSTRAKULIKULER TARI SISWA SEKOLAH DASAR - Gutama, Andika; Marliana, Desi; Ika Rahayu Nita, Cicilia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Traditional dance instruction in elementary schools plays an essential role in preserving cultural heritage while supporting students’ character development. However, participation in dance extracurricular activities remains relatively low because learning resources are limited and instructional approaches are often less engaging. This study examined the effect of Virtual Reality (VR)-assisted dolanan dance learning media on elementary school students’ interest in joining dance extracurricular activities. A quantitative approach with a quasi-experimental posttest-only control group design was employed. The participants were 30 elementary school students from SDN Kebonsari 2 who joined dance extracurricular activities and were equally divided into an experimental group and a control group (15 students each). Data were collected using a 20-item Likert-scale questionnaire measuring learning interest across five dimensions: enjoyment, curiosity, attention, active participation, and motivation. Instrument testing confirmed that all items were valid, with a Cronbach’s Alpha of 0.933, indicating excellent reliability. Data were analyzed using an independent-samples t-test. The results showed that VR-assisted learning media significantly increased students’ interest in dance extracurricular participation (p < 0.05). The experimental group achieved a higher mean score (67.67) than the control group (55.07), demonstrating the positive impact of the intervention. These findings suggest that integrating VR into dolanan dance instruction provides a more engaging learning experience and effectively enhances elementary school students’ interest in participating in dance extracurricular activities while supporting efforts to preserve traditional culture.